Authigenic pyrite and gypsum minerals in offshore Zhoushan sediments: morphology, formation, and environmental implications - Sun, Tiantian; Cao, Ke; Yin, Ping; Jiang, Xuejun; Tian, Yuan (Frontiers in Earth Science, 2023)
Offshore Zhoushan is a potential area for shallow gas resources in China, where authigenic pyrite is widely distributed. The content, size distribution, and morphology of pyrite are influenced by depositional conditions and are sensitive to environmental changes. In this study, the authigenic pyrites or gypsums of core JC-1 from offshore Zhoushan were investigated. Scanning electron microscopy was used to observe the pyrites, and various aggregations were identified. Changes in lithology, chlorine content, and stable isotope values of organic matter were analysed to indicate the evolution of ancient marine, floodplain estuary, tidal flat environments, and shallow marine sedimentary facies. The morphology and microcrystalline structure of these types of pyrites can be divided into spherical framboid aggregates, sub-euhedral aggregates, and microcrystalline euhedral pyrites with different sedimentary facies. Gypsum minerals and the coexistence of pyrite and gypsum were found in the enriched authigenic pyrites at the SMTZs. The sources of sulfate formed by authigenic gypsums may come from overlying seawater and the oxidation of pyrites, whereas calcium ions may come from the dissolution of carbonate or calcareous shells caused by local environmental acidification. The various aggregations of pyrites observed may be related to SO4-AOM in different environments. The findings suggest that authigenic gypsums are formed due to local environmental acidification, and the sources of sulfate formed may be from overlying seawater and the oxidation of pyrites. This study provides a new perspective for understanding the responses of different sedimentary environments to sea level rise and climate change.